Translocation Products in Acute Myeloid Leukemia Activate the Wnt Signaling Pathway in Hematopoietic Cells - Müller-Tidow, Carsten (American Society for Microbiology, 2004)
The acute myeloid leukemia (AML)-associated translocation products AML1-ETO, PML-retinoic acid receptor alpha (RARα), and PLZF-RARα encode aberrant transcription factors. Several lines of evidence suggest similar pathogenetic mechanisms for these fusion proteins. We used high-density oligonucleotide arrays to identify shared target genes in inducibly transfected U937 cells expressing AML1-ETO, PML-RARα, or PLZF-RARα. All three fusion proteins significantly repressed the expression of 38 genes and induced the expression of 14 genes. Several of the regulated genes were associated with Wnt signaling. One of these, plakoglobin (γ-catenin), was induced on the mRNA and protein level by all three fusion proteins. In addition, primary AML blasts carrying one of the fusion proteins significantly overexpressed plakoglobin. The plakoglobin promoter was cloned and shown to be induced by AML1-ETO, with promoter activation depending on the corepressor and histone deacetylase binding domains. The induction of plakoglobin by AML fusion proteins led to downstream signaling and transactivation of TCF- and LEF-dependent promoters, including the c-myc promoter, which was found to be bound by plakoglobin in vivo after AML1-ETO expression. β-Catenin protein levels and TCF and LEF target genes such as c-myc and cyclin D1 were found to be induced by the fusion proteins. On the functional level, a dominant negative TCF inhibited colony growth of AML1-ETO-positive Kasumi cells, whereas plakoglobin transfection into myeloid 32D cells enhanced proliferation and clonal growth. Injection of plakoglobin-expressing 32D cells into syngeneic mice accelerated the development of leukemia. Transduction of plakoglobin into primitive murine hematopoietic progenitor cells preserved the immature phenotype during colony growth, suggesting enhanced self-renewal. These data provide evidence that activation of Wnt signaling is a common feature of several balanced translocations in AML.